A4NH 2018 annual report highlights: Flagship 1 - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
This includes three highlights document for Flagship 1 of the CGIAR Research Program on Agriculture for Nutrition and Health: Highlight 1: Mind the Gap: Comparing Food Intake and Dietary Quality Highlight 2: Vegetable Consumption for Healthier Diets in Nigeria Highlight 3: Health and Sustainability: Assessing Food Systems